2012
DOI: 10.1016/j.biomaterials.2012.03.081
|View full text |Cite
|
Sign up to set email alerts
|

The degradation and clearance of Poly(N-hydroxypropyl-l-glutamine)-DTPA-Gd as a blood pool MRI contrast agent

Abstract: Although polymeric magnetic resonance imaging (MRI) agents have significantly improved relaxivity and prolonged circulation time in vivo compared with current imaging agents, the potential for long-term toxicity prevents their translation into the clinic. The aim of this study was to develop a new biodegradable, nonionic polymeric blood pool MRI contrast agent with efficient clearance from the body. We synthesized PHPG-DTPA, which possesses two potentially degradable sites in vivo: protein amide bonds of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…The results of this study suggest that PBS is the optimal choice of degradation solution for studying in vitro degradation properties of biological materials. In general, PBS is the most commonly used solution for degradation [17,21,22]. PBS has a stable pH value and osmotic pressure, without oxidation agents or any enzymes, so the degradation of the materials in PBS represents hydrolysis under physiological pH and osmotic pressure [23].…”
Section: In Vitro and In Vivo Degradation Of The Silk And Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study suggest that PBS is the optimal choice of degradation solution for studying in vitro degradation properties of biological materials. In general, PBS is the most commonly used solution for degradation [17,21,22]. PBS has a stable pH value and osmotic pressure, without oxidation agents or any enzymes, so the degradation of the materials in PBS represents hydrolysis under physiological pH and osmotic pressure [23].…”
Section: In Vitro and In Vivo Degradation Of The Silk And Degradationmentioning
confidence: 99%
“…Thus, the degradation of the materials in PBS relies upon hydrolysis under physiological pH and osmotic pressure [23]. Plasma is a better choice of degradation solution for the evaluation of in vitro degradation of materials [22]. The enzyme in tissue solution also play a crucial role in the degradation of the materials in animal tissues [10,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for the phenomenon might be that the hydrolysis and enzymolysis cleave the backbone and the side-chains of the gadolinium-copolymer, resulting in effectively excreting the degradable products with relative smaller molecular weight. The appearance of gadolinium (III) in the urine-bladder and feces indicated that the degradable products might be cleared from the mice through the renal and hepatobiliary metabolism [28][29][30].…”
Section: In Vivo Mri-tests Of Gadolinium (Iii)-complexesmentioning
confidence: 99%
“…The liver is a well perfused organ, and any T 1 effect of the contrast agent in the blood would cause the increased signal in the liver. Furthermore, ACL-A 2 -DOTA-Gd might be degraded in the body, and the released segments might diffuse into the liver interstitium [28], leading an increased signal in liver. In contrast to the rapid decreased signal of Gd-DOTA in the liver, the experimental group with injection of ACL-A 2 -DOTA-Gd presented the substantially increased signal, and the signal-time persisted for a longer period.…”
Section: In Vivo Mri-tests Of Gadolinium (Iii)-complexesmentioning
confidence: 99%